Information Management Behavior Related to the Self-Diagnosis of Mental Health Disorders by the Generation - Ivanna Clarissavitri; Mohamad Syahriar Sugandi (Green Publisher Indonesia, 2026)
The rapid growth of social media, particularly TikTok, has significantly influenced how Generation Z accesses and manages mental health information, leading to an increasing trend of self-diagnosis. However, previous studies have primarily focused on the impacts of self-diagnosis rather than the underlying information management process, creating a research gap. This study aims to explore how Generation Z manages mental health information on TikTok and how this process contributes to self-diagnosis behavior. Using an interpretive paradigm with a qualitative phenomenological approach, data were collected through in-depth interviews with Generation Z TikTok users and an expert informant, selected through purposive sampling. The data were analyzed using thematic analysis supported by NVivo 12. The findings reveal that information exposure initially occurs passively through TikTok’s algorithmic For You Page, which later develops into active information seeking. The interpretation and selection of information are largely influenced by emotional validation rather than scientific reasoning, while social interaction reinforces perceived credibility. This process leads to the formation of self-perception and self-diagnosis decisions. The study concludes that self-diagnosis is a subjective and gradual outcome of information management driven by media dependency. Theoretically, this research extends information behavior and media dependency frameworks, while practically emphasizing the need for improved digital mental health literacy and professional guidance.